Canadian medical student perceptions of the Choosing Wisely Canada campaign - Huo, Bright; Bolous, Yousef; Ramsay, Diane; McDermott, Emma; Sandila, Navjot; Campbell, Samuel (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: Medical student investment in resource stewardship (RS) is essential as resource overuse continues among physicians, but it is unclear whether this is influenced by hidden curriculum. This study investigated medical student perceptions of Choosing Wisely Canada (CWC).Methods: Canadian Medical students completed a bilingual questionnaire. Chi-square and student’s T-tests were used to analyze Likert responses capturing student attitudes toward questions grouped by theme, including the importance of the CWC campaign, the amount of CWC represented in undergraduate medical curriculum, the application of CWC recommendations in medicine, and the barriers which exist to student advocacy for CWC in practice.Results: There were 3,239/11,754 (26.9%) respondents. While most students (n = 2,720/3,171; 85.8%) endorsed the importance of CWC, few students felt that their institution had sufficiently integrated CWC into pre-clerkship (47.0%) and clerkship (63.5%) curricula. Overall, 61.4% of students felt that it is reasonable to expect physicians to apply CWC recommendations given the workplace culture in medicine. Only 35.1% of students were comfortable addressing resource misuse with their preceptor. The most common barriers included the assumption that their preceptor was more knowledgeable (86.4%), concern over evaluations (66.0%), and concern for their reputation (31.2%).Conclusions: Canadian medical students recognize the importance of CWC. However, many trainees feel that the workplace culture in medicine does not support the application of CWC recommendations. A power imbalance exists that prevents students from advocating for RS in practice.